Owner reported diseases of working equids in central Ethiopia. (13th October 2016) - Stringer, A. P.; Christley, R. M.; Bell, C. E.; Gebreab, F.; Tefera, G.; Reed, K.; Trawford, A.; Pinchbeck, G. L.
Summary: Reasons for performing study: Working horses, donkeys and mules suffer from numerous diseases and clinical problems. However, there is little information on what owners perceive as important health concerns in their working animals. Objectives: To identify and prioritise with owners the diseases and other health concerns in working equids in central Ethiopia using participatory methodologies. Study design: Participatory situation analysis (PSA). Methods: The study was conducted with carthorse‐ and donkey‐owners in 16 sites in central Ethiopia. Multiple participatory methodologies were utilised, including ranking, matrices and focus group discussions. Owners' perceptions on frequency, importance, morbidity and mortality of volunteered diseases and the clinical signs that owners attributed to each disease were obtained; information regarding the impact of these diseases and health concerns was also sought. Results: A total of 40 separate disease and health problems were volunteered by carthorse‐ and donkey‐owners. Horse‐owners volunteered a musculoskeletal syndrome (with the local name 'bird', clinical signs suggest possible disease pathologies including equine exertional rhabdomyolysis), colic and epizootic lymphangitis most frequently, whereas donkey‐owners volunteered sarcoids, nasal discharge and wounds to occur most frequently. One problem (coughing) was volunteered frequently by both horse‐ and donkey‐owners. Owners demonstrated knowledge of differing manifestations and severity of these problems, which resulted in differing impacts on the working ability of the animal. Conclusions: Although many of the diseases and clinical signs had been previously reported, this study also identified some previously unreported priorities such as rabies in donkeys, an unidentified musculoskeletal syndrome in horses and respiratory signs in both horses and donkeys. The information gathered during this participatory study with owners may be used to inform future veterinary and educational programme interventions, as well as identify future research priorities.